2013
DOI: 10.1007/s00405-013-2548-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced sleep endoscopy: a two drug comparison and simultaneous polysomnography

Abstract: The purpose of the present study was to compare pharyngeal and polysomnographical findings during drug-induced sleep endoscopy (DISE) performed with either propofol or midazolam as a single sedative agent. It is prospective, non-randomized, double-blinded case series study. Sixteen patients with sleep disordered breathing were sedated first with propofol and after full wake up with midazolam. Simultaneous polysomnography (PSG) was performed. We compared the zones of obstruction and vibration found with both dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 37 publications
1
31
1
1
Order By: Relevance
“…Carrasco‐Llatas et al compared midazolam and propofol in the same patients with OSA and did not observe differences in the degree and pattern of obstruction sites, excepted the velum, thus opposing our findings. Yoon et al showed that in patients sedated with propofol and dexmedetomidine during DISE, the agreement and correlation regarding UA collapse was excellent for all obstruction sites regardless of whether light (65 to 75) or deep (50 to 60) sedation was used .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Carrasco‐Llatas et al compared midazolam and propofol in the same patients with OSA and did not observe differences in the degree and pattern of obstruction sites, excepted the velum, thus opposing our findings. Yoon et al showed that in patients sedated with propofol and dexmedetomidine during DISE, the agreement and correlation regarding UA collapse was excellent for all obstruction sites regardless of whether light (65 to 75) or deep (50 to 60) sedation was used .…”
Section: Discussioncontrasting
confidence: 99%
“…Different drugs have been used to induce sedation during DISE, including midazolam, propofol and dexmedetomidine . All drugs present specific advantages and disadvantages with differential effects on respiratory physiology …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, have compared propofol and, after recovery, with midazolam, finding that using a continuous perfusion, there is a good agreement; in this report, outpatient physical exam did not correlate with drug-induced sleep findings 44 . However, others believe that more work is needed to standardize the anesthesia side of DISE 45 .…”
Section: The Vote Classificationmentioning
confidence: 45%
“…2 When performed under specific conditions and guidelines, propofol-induced sedation correlates most closely with deeper levels (stage N2) of non-rapid eye movement (NREM) sleep and maintains a similar AHI as compared with physiologic sleep. 3,4 Studies of sleep endoscopy have demonstrated validity, test-retest reliability, and interrater reliability. 5,6 Recent data suggest that utilization of DISE can improve treatment outcomes with oral appliances.…”
Section: Novel Diagnostic Evaluation Approachmentioning
confidence: 99%